2017
DOI: 10.1016/j.jcin.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Dual Antiplatelet Therapy for 6 Versus 18 Months After Biodegradable Polymer Drug-Eluting Stent Implantation

Abstract: Six months of DAPT was not inferior to 18 months of DAPT following implantation of a DES with a biodegradable abluminal coating. However, this result needs to be interpreted with caution given the open-label design and wide noninferiority margin of the present study. (Nobori Dual Antiplatelet Therapy as Appropriate Duration [NIPPON]; NCT01514227).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 24 publications
1
98
0
1
Order By: Relevance
“…Studies have shown that shorter DAPT length could be reasonable for BP‐DES. In the NIPPON study (biolimus BP‐DES), there was no significant increase in cardiovascular adverse events between the 6‐ and 18‐month DAPT . The I‐LOVE‐IT 2 study (sirolimus BP‐DES) showed no significant difference in TLF and total adverse events between the 6‐ and 12‐month DAPT groups .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have shown that shorter DAPT length could be reasonable for BP‐DES. In the NIPPON study (biolimus BP‐DES), there was no significant increase in cardiovascular adverse events between the 6‐ and 18‐month DAPT . The I‐LOVE‐IT 2 study (sirolimus BP‐DES) showed no significant difference in TLF and total adverse events between the 6‐ and 12‐month DAPT groups .…”
Section: Discussionmentioning
confidence: 95%
“…In the NIPPON study (biolimus BP-DES), there was no significant increase in cardiovascular adverse events between the 6-and 18-month DAPT. 22 The I-LOVE-IT 2 study (sirolimus BP-DES) showed no significant difference in TLF and total adverse events between the 6-and 12-month DAPT groups. 23 The GLOBAL LEADERS study (biolimus BP-DES) compared 1-month DAPT, followed by ticagrelor monotherapy with standard 1-year DAPT, and found no difference between cardiovascular events and ST, 24 which also indicated the possibility of short-term DAPT.…”
Section: Clinical Outcomesmentioning
confidence: 93%
“…To illustrate our methods, we perform an analysis of long-term follow-up of the NIPPON trial. 20 The study was designed to evaluate the noninferiority of the short-term DAPT (6 months) compared to long-term DAPT (18 months) in patients with drug eluting stents. The primary endpoint was time to the first occurrence of all-cause mortality, MI, stroke, or major bleed by 18 months.…”
Section: Examplementioning
confidence: 99%
“…These trials were powered to look for difference in bleeding, and due to the low ischemic event rates, any conclusions drawn to qualify the efficacy would be inaccurate. More recently, NIPPON trial 56 was performed in Japan using bioabsorbable polymer-based DES. This trial tested for non-inferiority of 6-month DAPT vs. 18month DAPT, and randomized 3775 patients.…”
Section: Table 4 Comparative Features Of Randomized Controlled Trialsmentioning
confidence: 99%